1995
DOI: 10.1159/000217954
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Luteinizing Hormone on Cell Growth and CA125 Secretion of Primary Epithelial Ovarian Carcinomas in vitro

Abstract: In the present study, the influence of human luteinizing hormone (hLH) on the growth and the CA 125 secretion of primary ovarian carcinoma cell cultures derived from 11 previously untreated patients was investigated. Two different patterns of in vitro growth of unstimulated ovarian carcinoma cells could be detected: 5 cell cultures in which no changes of cell number were observed during an incubation period of 6 days (group A) and 6 cell cultures which grew without any hormonal support (group B). All tumors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Unlike the uncertainty as to the origin of high gonadotropin concentrations in the fluid from epithelial tumors of the ovary, sample evidence has been provided that gonadotropins support cell proliferation (Wimalsena et al 1992, Kurbacher et al 1995, Schiffenbauer et al 1997, Syed et al 2001 through receptors expressed by tumor cells (Mandai et al 1997, Parrot et al 2001.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the uncertainty as to the origin of high gonadotropin concentrations in the fluid from epithelial tumors of the ovary, sample evidence has been provided that gonadotropins support cell proliferation (Wimalsena et al 1992, Kurbacher et al 1995, Schiffenbauer et al 1997, Syed et al 2001 through receptors expressed by tumor cells (Mandai et al 1997, Parrot et al 2001.…”
Section: Resultsmentioning
confidence: 99%
“…One of the predominant theories is a gonadotropin theory that circulating levels of pituitary gonadotropins increase the risk of malignancy and that pregnancies and oral contraceptives protect by suppressing secretion of these hormones (Gardner 1961, Stadel 1975. Based on recent studies, treatments with FSH and LH/hCG seem to result in growth stimulation in normal, immortalized OSE and some ovarian cancer cells in a dose-and time-dependent manner in vitro (Wimalasena et al 1992, Kurbacher et al 1995, Kraemer et al 2001, Ohtani et al 2001, Parrott et al 2001, Syed et al 2001, Choi et al 2002, although there are controversial reports (Wimalasena et al 1991, Venn et al 1995, Ivarsson et al 2001, Tourgeman et al 2002. Despite these observations, whether gonadotropins may play a role in normal OSE biology and ovarian tumorigenesis remains to be fully elucidated and the exact mechanism of the response to gonadotropins is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have shown that hCG can stimulate ovarian cancer growth [3][4][5][6]. Respective receptors have been detected immunohistochemically as well as on mRNA basis [7,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In their experiments, tumors could only be induced when LH increased which led them to speculate that LH Steinmeyer/Berkholz/Gebauer/Jäger plays the crucial part for tumor development. Experiments with tissue cultures have shown that the growth of human ovarian cancer cell lines is stimulated by hCG and LH [3][4][5][6]. This was the case especially with cell lines derived from highly differentiated ovarian carcinomas.…”
Section: Introductionmentioning
confidence: 99%